The Role of Pentahelix Actors for Sawahlunto City to be Deemed a Unesco World Heritage - Reza Permadi; Fahriza Junizar; Nurul Aldha Mauliddinna Siregar; Ute Lies Siti Khadijah (Institut Pariwisata dan Bisnis Internasional, 2021)
The coal mine closures have turned Sawahlunto into an idle city. By integrating the post-mining sites landscape and the Dutch colonial architecture heritage, Sawahlunto becomes a city of a kind. Therefore, the local government and the legislature (DPRD) as well as other stakeholders created a vision for Sawahlunto as a “A Cultural Tourism Mining City” in 2020, set in Local Government Regulation (PERDA) No 2 of 2001. The year 2020 was set as a target to motivate the local government and stakeholders to achieve the vision. As a matter of fact, Sawahlunto has been included as a World Heritage site by UNESCO as of 2019. This research aims to understand the role of stakeholders in developing and rebranding Sawahlunto, by using the Pentahelix model. This research uses a qualitative method along with the case study approach as well as utilizing interviews, observations and archival study as the types of research methodology. Finally, the result of this research shows that the stakeholders carry out their roles well and fully support the vision of Sawahlunto city.